Aromatypicity of Austrian Pinot Blanc Wines - Philipp, Christian (Molecules, 2020)
Pinot blanc is a grape variety found in all wine-growing regions of Austria. However, there are only few scientific studies which deal with the aroma of wines of this variety. In the course of this project, the relationship between aroma profile and the typicity of Austrian Pinot blanc wines was studied. The aim was to describe the typicity and to find significant differences in aroma profiles and aroma descriptors of typical and atypical Pinot blanc wines. Since the typicity of a jointly anchored prototype is embedded in the memory, typical attributes for Austrian Pinot blanc wines were first identified by consumers and experts or producers. According to this, 131 flawless commercial Austrian wines of the variety Pinot blanc of the vintages 2015 to 2017 were analysed for more than 100 volatile substances. The wines of the vintages 2015 to 2017 were judged by a panel of producers and experts for their typicity; furthermore, the wines of the vintage 2017 were also evaluated by a consumer panel and a trained descriptive panel. Subsequently, typical and atypical wines were described by the trained descriptive panel. It was found that Pinot blanc wines typical of Austria showed significantly higher concentrations of the ester compounds ethyl hexanoate, ethyl butanoate, ethyl octanoate, ethyl decanoate, methyl hexanoate, hexyl acetate and isoamyl acetate, while atypical wines had higher concentrations of free monoterpenes such as linalool, trans-linalool oxide, nerol oxide, nerol and alpha-terpineol. The sensory description of typical Pinot blanc wines was significantly more pronounced for the attribute “yellow pome fruit”, and tended to be more pronounced for the attributes “green pome fruit”, “pear”, “walnut”, “pineapple”, “banana” and “vanilla”, while the atypical Pinot blanc wines were described more by the attribute “citrus”. These findings could help to ensure that, through targeted measures, Austrian Pinot blanc wines become even more typical and distinguish themselves from other origins such as Germany or South Tyrol through a clear concept of typicity.